2022
DOI: 10.1108/k-11-2021-1119
|View full text |Cite
|
Sign up to set email alerts
|

Chatbots in the frontline: drivers of acceptance

Abstract: PurposeBy extending the service robot acceptance model (sRAM), this study aims to explore and enhance the acceptance of chatbots. The study considered functional, relational, social, user and gratification elements in determining the acceptance of chatbots.Design/methodology/approachBy using the purposive sampling technique, data of 321 service customers, gathered from millennials through a questionnaire and subsequent PLS-SEM modeling, was applied for hypotheses testing.FindingsFindings revealed that the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 149 publications
(379 reference statements)
0
2
0
Order By: Relevance
“…Other studies have yielded similar results, such as [28,35,36,60,61,74]. In addition, Kumar and Silva [55] found that perceived ease of use (expected effort) positively affects students' attitudes toward accepting the use of chatbots in learning, as did many other studies [16,35,52,60,61,74]. Regarding the factor of attitude, several studies indicate that students' attitudes toward chatbots are a main predictor of their acceptance and use behavior [22,35,52,56,59,75].…”
Section: Relationships In the Tammentioning
confidence: 57%
See 1 more Smart Citation
“…Other studies have yielded similar results, such as [28,35,36,60,61,74]. In addition, Kumar and Silva [55] found that perceived ease of use (expected effort) positively affects students' attitudes toward accepting the use of chatbots in learning, as did many other studies [16,35,52,60,61,74]. Regarding the factor of attitude, several studies indicate that students' attitudes toward chatbots are a main predictor of their acceptance and use behavior [22,35,52,56,59,75].…”
Section: Relationships In the Tammentioning
confidence: 57%
“…For example, Chen et al [31] confirm in their study that the perceived usefulness (expected benefit) of chatbots positively affects students' attitudes toward chatbot acceptance and use behavior in learning. Other studies have yielded similar results, such as [28,35,36,60,61,74]. In addition, Kumar and Silva [55] found that perceived ease of use (expected effort) positively In the context of chatbot use in education, the TAM is by far the most used model for investigating both students' and teachers' perceptions of chatbot use in learning [31,62].…”
Section: Relationships In the Tammentioning
confidence: 70%
“…Thus, it is observed that in the context of higher education, AI technologies can enhance the learning experience by providing personalized, adaptable, and data-driven solutions that help students learn more efficiently and effectively (AL KA 'BI, 2023;HALAGATTI et al, 2023b;NAVEENKUMAR et al, 2023;SANTOS et al, 2023). AIbased educational tools such as chatbots, virtual assistants, and automated assessment systems can save time and improve the quality of education by providing immediate feedback to students (ASLAM et al, 2022;EBADI;AMINI, 2022;JEON, 2021JEON, , 2022YU, 2023;PALLATHADKA et al, 2022).…”
Section: • Educational Data Analysismentioning
confidence: 99%
“…With artificial intelligence tools, personal and technical competencies of candidates are measured, away from individual prejudices (Aslam et al., 2022). According to the results of the research, human resources are the most suitable candidate (Mirowska, 2020).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Chatbot solutions are particularly well suited for interviews because they can provide a much more accurate picture of how someone would perform in a given role, taking context into account. Rather than relying solely on the job applicant's ability to verbally explain things in a static and emotional situation, chatbots create an environment where the candidate can sit back and relax while still demonstrating their knowledge and aptitude in a nonintimidating environment (Aslam et al., 2022). This task‐based interview process allows HR personnel to accurately assess potential hires while also improving overall satisfaction with interviewing experiences.…”
Section: Introductionmentioning
confidence: 99%